Pelaksanaan Hak Ex Officio Hakim Atas Nafkah Iddah, Mut’ah, Hadlonah dan Madhiyah dalam Perkara Cerai Gugat Ditinjau dari Perma Nomor 3 Tahun 2017: Analisis Putusan No.2675/Pdt.G/2023/PA.Kab.Kdr - Ayu Cahyani; Muhammad Fajar Sidiq Widodo; Mohammad Hendy Musthofa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The ex officio right is the right possessed by the judge to decide more or other than what is submitted in the lawsuit, with the ex officio right, the judge can concretely impose decisions that prevent women from becoming victims of post-divorce economic violence while still being guided by the limitations set out in the applicable laws and regulations. economic rights of women after divorce such as iddah maintenance, mut'ah maintenance, hadlonah maintenance and madhiyah maintenance. This research uses empirical research with a legal sociology approach. The data sources obtained are secondary data sources and primary data sources. While the acquisition of data obtained from the contents of the decision, the results of interviews with Religious Court Judges who decided the case, as well as other supporting literature. And the research stage is carried out by conducting interviews with sources, compiling data from the results of interviews, and making research reports. The results of this discussion can be concluded as follows: The application of the ex officio rights of the panel of judges in case number 2675/Pdt.G/2023/PA.Kab.Kdr is in accordance with PERMA No. 3 of 2017. Although the Plaintiff has filed for the fulfillment of the rights of iddah, mut'ah, hadlanah, and madhiyah maintenance, but in the trial there were differences in the facts submitted by the Plaintiff and the Defendant so that in order to resolve the debate, the panel of judges used their ex officio rights to provide legal certainty and justice for the Parties